Efek Daun Kelor Terhadap Ukuran Lingkar Skrotum dan Libido Sapi Bali - Muh. Arsan Jamili; Abd. Latief Toleng; Muhammad Yusuf (Fapetrik-UMPAR, 2020)
The reproductive process's success is mostly determined by the conditions of the male and female who are married. Male quality is determined by testicular size, libido, and, most importantly, semen quality. One of the factors that determine testicular size and libido is nutrition. Moringa is a type of vegetable that has excellent nutritional content. This study aimed to determine the effect of Moringa leaves on scrotum circumference and libido of Bali cattle. This study used 12 male Bali cows with a bodyweight of 150-200 kg aged 2-4 years, divided into two treatments: cows without Moringa leaves and cows given Moringa leaves. Moringa leaves (room dried) were given as much as 0.1% of body weight in the morning for 13 weeks. Data were collected once a week. Furthermore, the data obtained were analyzed using SPSS with the T-Student Independent Sample test. The results showed that cows given Moringa leaves were not significantly different from cows that were not given Moringa leaves (control treatment) in the initial seven periods of the study (P> 0.05). Still, after that period (weeks 8-13), there was a significant effect. very significant (P <0.01). In contrast to the libido, the scrotal circumference size of Bali Cows given Moringa leaves was significantly different from the control treatment (P <0.01). This means that Moringa leaf supplementation can increase the scrotal circumference and libido at the 8th week of Moringa leaf supplementation.